A program and session evaluation of student-athletes' experiences participating in a mental illness destigmatization intervention - Chow, G. M.; Gabana, N. T.; Cox, C.; Cooper, B. T.; Bird, M. D. (Journal of Clinical Sport Psychology, 2025)
Evidence-based stigma reduction interventions for student-athletes exist, but researchers have focused on assessing their effectiveness with little attention paid to understanding how participants experience such programs. The current study aimed to qualitatively evaluate a mental illness destigmatization intervention delivered to 35 National Collegiate Athletic Association Division I student-athletes. The program consisted of four weekly 1 hr empirically based sessions. Program-level results showed that participants increased their understanding of student-athlete mental health and identified actionable ways to combat stigma. Session-level results revealed intervention components impacted knowledge and application consistent with their theoretical underpinnings (i.e., mental health literacy). Practical guidelines based on the findings suggest stigma reduction interventions aimed at student-athletes should provide information specific to the athletic context (i.e., common symptoms experienced by athletes), consider content that moves beyond mental health literacy (e.g., contact-based interventions), and present opportunities for participants to apply what they have learned (i.e., roll play displaying empathy).